Towards Integration: a Three-Dimensional Approach to Moral Education in the Philosophies of al-Ghazālī and Kant = nḥū āltkāml: rūʾīa ṯlāṯīa ālāʾbʿād lltrbīa ālāʾḫlāqīa fī āltkāml bīn flsftī ālġzālī ūkānṭ - Wahab, Abdurrahman Ahmad (Journal of Islamic ethics, 2025)
This study offers a constructive synthesis of the moral epistemologies of Abū Ḥāmid al-Ghazālī (d. 505/1111) and Immanuel Kant (d. 1804), two philosophers rooted in distinct intellectual traditions yet united by a shared concern with the conditions of moral agency. Moving beyond thematic comparison, this study integrates al-Ghazālī’s prophetic faculty with Kant’s faculties of cognition to formulate a Three-Dimensional Ethical Framework. This framework articulates a more comprehensive account of moral agency - one that preserves the rational autonomy central to Kant’s ethics while incorporating the supra-rational dimension essential to al-Ghazālī’s spiritual pedagogy. Drawing in part on Seyyed Hossein Nasr’s (b. 1933) perennialist reading of Islamic epistemology, the paper articulates a holistic model of moral education that reconciles reason and revelation. The result is a pedagogical model that bridges rational and prophetic approaches to ethics, reimagining moral education as a transformative journey engaging the full human being - reason, character, and soul - in the pursuit of moral and human perfection.